Sport psychology services to high performance athletes during COVID-19 - Schinke, R.; Papaioannou, A.; Henriksen, K.; Si, G.; Zhang, L.; Haberl, P. (International Journal of Sport and Exercise Psychology, 2020)
These are trying times for us all. COVID-19 has altered our lives as citizens. The changes associated with the current pandemic have presented sport and exercise psychologists with many challenges and opportunities related to sport performance, physical activity and health. Here, we focus on what was, and is presently, being encountered by mental performance consultants in relation to the aspiring Olympic athletes they are supporting.